Jail register, 1931-1939 (1931)
Bound ledger of arrests conducted by the San Luis Obispo County Sheriff's office between November 1931 to June 1939. The ledger begins with an index, sorted first by first letter of arrested persons' last name, then further sorted by date of arrest. The register of arrests begins on page 56 of the digitized PDF. Each "page" spans two physical pages, because each record in the register spans two physical pages. The categories in register are: Number, Name, Date Received, Arresting Officer, Booking Officer, Charge, Sex, Age, Race, Place of Birth, Occupation, Residence (City; Length of time in: County, State, U.S.A.), Trial Judge, Court, Sentence, Date of Sentence, Commitment Received, Passed Out: date, hour, no. meals, how.